In vitro study on the effect of plant extract mixture and its individual constituents towards single- and dual-species biofilms / Zaleha Shafiei - Zaleha, Shafiei (2018)
The plant extract mixture (PEM) and its individual constituents (Psidium sp., Mangifera sp. and Mentha sp.) were investigated in vitro for their anti-plaque and anti-caries potential towards Streptococcus sanguinis ATCC BAA-1455 and Streptococcus mutans ATCC 25175 in single- and dual-species biofilms. The ability of these plant extracts as antibacterial, anti-adherence agents and in reducing bacterial population in biofilms, cellsurface hydrophobicity and acid production activities were determined. The reduction in expression of adhesins genes of S. mutans (gtfB, gtfC, gbpB and spaP) due to treatment with PEM in planktonic and biofilms conditions was also determined using Real-time RTPCR analysis. The anti-adherence and anti-biofilm assays were determined based on bacterial population retained in biofilms using the percentage colony forming unit per ml (CFU/ml) and visualised under Scanning Electron Microscope (SEM). The phenolic compounds of the plant extracts were assessed by Total Phenolic Content (TPC) and UPHLCMS/MS analysis. Fold change in the expression of S. mutans adhesins-genes (gtfB, gtfC, gbpB and spaP genes) relative to the internal control in the PEM-treated samples compared to the untreated control was calculated using relative quantification of 2 -∆∆Ct method. All the plant extracts exhibited antibacterial activities with the PEM (MIC value of 1.96 mg/ml) was the highest and exhibiting synergistic interaction. At sub-MIC value of 0.5 mg/ml, the plant extracts highly reduced the bacterial adherence towards experimental pellicle and bacterial populations of S. sanguinis and S. mutans in single- and dual-species biofilms. PEM significantly reduced adherence capacity by 48-49% and creating equilibrium communities of S. sanguinis and S. mutans, and was reflected in the SEM analysis. In normal condition, sucrose enhanced the growth of S. mutans (by 107 CFU/ml) and restricted S. sanguinis (105 CFU/ml) growth. However, the equal proportion (106 CFU/ml) of the two bacteria was observed in dual-species biofilms grown in the absence and presence of sucrose. PEM and Mangifera sp. effectively reduced S. mutans iv population in single- and dual-species biofilms grown in the absence of sucrose. In the presence of sucrose, PEM effectively reduced both the two types of bacterial population in single-species biofilm but S. mutans was hard to remove compared to S. sanguinis in dualspecies biofilms. PEM exhibited the highest potential in reducing cell-surface hydrophobicity and acid production of the two types of bacteria (in single- and dualspecies). PEM as a potential anti-plaque and anti-caries agent correlates with the synergistic interaction of different active compounds present in the extract. PEM strongly reduced the expression of gtfB genes of S. mutans by 2.04-fold (in singly, planktonic condition) and by 2.08-fold (in dual-species, biofilm condition). The expression of gtfC, gbpB and spaP genes were upregulated in both planktonic and biofilm conditions allowing the S. mutans to adhere and form biofilms in the presence of sucrose. In conclusion, the results strongly supported that the PEM is a better candidate as the anti-plaque and anticaries agent and could be incorporated in oral healthcare product with further validation of the product in vivo.